Survival Analysis of Chronic Kidney Disease (CKD) Patients Undergoing Hemodialysis at RSUD Ratu Zalecha Martapura - Azzahro, Nasywa Nabilah; Anggraini, Dewi (Jurnal Matematika, Statistika dan Komputasi, 2025)
The kidneys play an important role in excreting the body's metabolic waste. The progressive decline in kidney function triggers Chronic Kidney Disease (CKD) which can be fatal if it’s not treated by undergoing regular hemodialysis or kidney transplantation. Research related to the effectiveness of the survival time of CKD patients is still limited, therefore this study aims to analyze the survival of CKD patients undergoing hemodialysis at Ratu Zalecha Martapura Hospital using survival analysis. The data collection method used purposive sampling. The research data were obtained from secondary source of medical records of 335 CKD patients who underwent hemodialysis during the observation in period from January 2022 until October 2024. The survival analysis methods used include Kaplan-Meier and Log-Rank tests for estimation of the survival function and Cox Proportional Hazard regression models by comparing 3 methods of handling co-occurrence (ties) namely Breslow, Efron, and Exact to identify factors that affect patient survival. The results showed that CKD patients without comorbidities had a higher survival chance than patients with hypertension, diabetes mellitus, and cardiovascular disease. In comparing the methods of handling ties, Exact method was the most appropriate for the data with the smallest Akaike Information Criterion (AIC) value of 481.3439. In addition, it was found that the factors that significantly influenced the length of CKD patient’s survival were hypertension status, diabetes mellitus status, and cardiovascular status.